1997
DOI: 10.1161/01.atv.17.7.1283
|View full text |Cite
|
Sign up to set email alerts
|

PDGF Receptor Protein Tyrosine Kinase Expression in the Balloon-Injured Rat Carotid Artery

Abstract: Platelet-derived growth factor (PDGF) receptor gene expression has previously been demonstrated in balloon-injured rat carotid arteries to be regulated during repair of carotid injury. In the present study we showed that PDGF receptor protein expression and phosphorylation are changed over time after carotid artery injury. In control and 2-day-postinjury vessels, expression of PDGF alpha receptor protein was readily detectable, whereas PDGF beta receptor expression appeared very low. Between 2 and 7 days posti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
29
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 20 publications
1
29
0
Order By: Relevance
“…All of these results correspond well with our finding of moderately upregulated PDGFR␤ expression on day 3 after injury and a marked increase in receptor expression after 2 weeks ( Figure 5A). Our preliminary experiments after immunoprecipitation of PDGFR␤ validated that the band migrating at 190 kDa is PDGFR␤, as was shown by Panek et al 40 and by the findings in the present study (190 kDa and the similar band location after immunoblotting with anti-PDGFR␤ and anti-phosphotyrosine antibodies; compare Figure 5A and 5B).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…All of these results correspond well with our finding of moderately upregulated PDGFR␤ expression on day 3 after injury and a marked increase in receptor expression after 2 weeks ( Figure 5A). Our preliminary experiments after immunoprecipitation of PDGFR␤ validated that the band migrating at 190 kDa is PDGFR␤, as was shown by Panek et al 40 and by the findings in the present study (190 kDa and the similar band location after immunoblotting with anti-PDGFR␤ and anti-phosphotyrosine antibodies; compare Figure 5A and 5B).…”
Section: Discussionsupporting
confidence: 91%
“…We, 25 as well as others, 24,40 have previously shown that balloon injury upregulates overall tyrosine phosphorylation in vascular SMCs. In accordance with these early findings, we have shown in the present study (Figure 5B) that tyrosine phosphorylation of PDGFR␤ (190 kDa) and of several other proteins was increased.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…2,4,16,26,29 -35 Although alpha PDGFR was not detected in baboon arteries in the present study, low levels of this receptor have been detected in the media of the rat carotid artery and in the neointima of healing vascular grafts in baboons. 16,29,32,33,35 Alpha PDGFR expression by medial SMC could be functionally important because PDGF A chain, which only interacts with the alpha receptor, has been routinely observed in atherosclerotic plaques and in medial cells after injury. 1,2,16,26,29 To address the relative importance of alpha and beta PDGFR in the vascular response to injury, we used the isotype-matched neutralizing mAbs 2H7C5 and 2A1E2 directed against alpha and beta PDGFRs, respectively.…”
Section: Discussionmentioning
confidence: 99%